Evasion in a distance-educacion pedagogy course: a glimpse from the tutors’ perspective - Cordeiro, Gisele do Rocio; Gisi, Maria Lourdes (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This research has, as object of study, the evasion in university education, a problem that is due to multiple causes related to factors, which may be intern and extern to the universities. Besides the difficulties in access from the young students, we have noticed in the data from INEP (2016) a striking difference in the relation to the beginners and the concluders, demonstrating significant evasion. The study has, as main theoretical-methodological reference, the writings by Bourdieu (2000; 2003; 2010; 2014); Bourdieu; Passeron (2016) and was carried out upon the students’ data analyses which refer to the reasons presented to justify the interruption of the studies of a distance-education pedagogy course. The professors/tutors’ data were also analyzed through the replies of a questionnaire. The analysis has taken as criterion the factors related to the economic conditions, the course and the students’ profile. The research shows the reasons for evasion and its relation to the different factors, with greater emphasis on the learning difficulties.